Association Between 2-Hour Postprandial Blood Glucose Levels and Acid Fast Bacilli Positivity - Azhari Muslim; Karbito Karbito; Hardono Hardono (MEDICA (International Medical Scientific Journal), 2026)
Pulmonary tuberculosis (TB) and hyperglycemia have a bidirectional relationship, whereby impaired glucose metabolism can weaken cellular immunity and potentially increase the bacterial burden, resulting in a higher degree of acid-fast bacilli (AFB) positivity. Although the 2-hour postprandial blood glucose (2h-PPBG) test is a practical indicator of glucose intolerance, its association with AFB positivity in pulmonary TB patients remains inadequately explored. This study aimed to analyze the relationship between 2h-PPBG levels and the degree of AFB positivity among patients with pulmonary TB. A cross-sectional study was conducted at the Sukamaju Community Health Center in 2024 involving 60 adult patients (≥18 years) diagnosed with pulmonary TB and diabetes mellitus. Participants were selected based on confirmed pulmonary TB diagnosis and complete blood glucose records. Data were analyzed using Spearman’s correlation test and binary logistic regression. The results demonstrated a strong and statistically significant positive correlation between 2h-PPBG levels and the degree of AFB positivity. Logistic regression analysis indicated that every 10 mg/dL increase in 2h-PPBG was associated with a 9.3% increase in the odds of higher AFB positivity. In conclusion, elevated 2h-PPBG levels were significantly associated with greater AFB positivity among patients with pulmonary TB and diabetes mellitus. These findings highlight the importance of routine glycemic screening and optimal glucose control as part of comprehensive tuberculosis management to reduce disease severity and improve treatment outcomes.